PERUBAHAN TRADISI KUBUR BATU MASYARAKAT ADAT MARAPU PADA ERA MODERNISASI DI KAMPUNG RAJA KECAMATAN KAMBERA KOTA WAINGAPU - Wadu, Febryanto; Suka Arjawa, I Gusti Putu Bagus; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The tradition of the stone grave for Sumbanese society is cultural habit as a final form of respect for the deceased. However, the tradition of the stone tomb has changed. The change happens because the society has experienced a change of mindset that is from traditional to a modern one in a sense that society does not eliminate the customary cultural heritage (Merapu). The problems that are examined in this research are: 1) why there is a change of stone tradition of indigenous people in the era of modernization in Kampung Raja, 2) how the impact of changing the tradition of stone grave of indigenous peoples in the era of modernization in Kampung Raja. The purpose of this research is to answer the problem by using qualitative research method. The theory used is the theory of social change Wiliam F Ogburn. Based on the results of this study indicates that the tradition of the stone tomb has changed but did not eliminate the tradition. People still do it but in a simpler and less costly way. The changes have a positive impact on the community, among others, the positive impact is to reduce conflicts between families, reduce poverty and improve economic and people's habits into positive one. . Keywords: stone tomb tradition, marapu, social change, modernization.